Jewish Continuity and the Canadian Census - Robert Brym (Canadian Jewish Studies)
Some researchers view acculturation—the assimilation of a minority culture into a dominant culture—as a force that undermines the continuity of Jewish communities. Other researchers view acculturation as an adaptive mechanism that permits Jewish communities to survive and flourish in modern environments. This paper examines what national counts of Canadian Jews can tell us about these competing interpretations of the effect of acculturation. It focuses on Canada’s 2011 and 2021 national population counts in an effort to decipher whether they point to continuity or decline. The paper finds that both processes are reflected in recent census data, with continuity the predominant outcome.